MANAGEMENT INFORMATION SYSTEMS FOR ORGANIZATIONAL COMPETITIVE ADVANTAGE - Budiman Budiman (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2021)
Over the past few years, the topic of competitive advantage has been the focus of much discussion. Competitive advantage can be achieved through processing physical resources, but virtual resources can also play a big role. Organizations are formal, stable structures that take resources from the environment and process them to produce outputs. Organization is also a social structure because it is a collection of social elements. A more realistic picture of organizational behavior is a set of rights, obligations and responsibilities that are balanced over a period of time through conflict and conflict resolution. Information systems and organizations influence each other, in order to provide the information needed in a particular part that is important to the organization. Organizations on the other hand must also be alert and open to the influence of information systems in order to benefit from new technology. Information technology provides tools for managers to complete both their new and traditional roles. Finding ways to utilize information technology to achieve competitive advantage at the business, corporate and industry level is a key responsibility for managers. Technology today can lead to efficiency and major organizational changes and reduce transaction costs and can also be a source of competitive advantage. Information technology offers new ways to organize work and use information that can increase wealth and sustain organizational life.